The Relationship Between Caffeine Intake and Cognitive Behavioral Therapy for Insomnia Efficacy in Patients With Chronic Insomnia - Yeonsoo Kim; Tae-Joon Kim; JaeWook Jeong; Jung-Won Shin (Journal of Sleep Medicine, 2026)
Objectives: Cognitive behavioral therapy for insomnia (CBT-I) is the first-line treatment for chronic insomnia; however, individual responses vary. Although caffeine disrupts sleep, its effect on CBT-I outcomes remains unclear. This study investigated the relationship between caffeine consumption and efficacy of CBT-I.Methods: This retrospective study included 37 adults with chronic insomnia who completed a standardized 4-week CBT-I program. The participants were classified into the caffeine (n=19) and non-caffeine (n=18) groups. Insomnia severity and sleep quality were assessed before treatment and 2 weeks after completion using the Insomnia Severity Index (ISI) and Pittsburgh Sleep Quality Index (PSQI).Results: CBT-I significantly improved ISI and PSQI scores over time in both groups (p7 points) or PSQI (≥3 points), did not differ between groups. However, the caffeine group consistently reported poorer subjective sleep quality and greater daytime dysfunction than the non-caffeine group at both time points.Conclusions: CBT-I effectively improved insomnia severity and sleep quality irrespective of daily caffeine consumption. While caffeine intake does not appear to reduce the overall CBT-I efficacy, persistent subjective sleep impairment and daytime dysfunction among caffeine consumers suggest that individualized caffeine education may help optimize perceived treatment outcomes.